Association of maxillary sinus volume and deviated nasal septum (DNS) assessed by computed tomography (CT) in patients with chronic maxillary sinusitis in tertiary care hospital of Nepal - Jaiswal, Pooja; KC, Sudeep; Shrestha, Shreejana; Dwa, Yogita (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Deviated nasal septum (DNS) is a common anatomical variation frequently associated with chronic maxillary rhinosinusitis (CRS). Changes in nasal airflow dynamics due to DNS can alter sinus ventilation and muco-ciliary drainage, potentially affecting maxillary sinus volume. Radiological assessment, particularly computed tomography (CT), plays a vital role in evaluating sinonasal anatomy and pathology. Method: This cross-sectional, prospective study was done in Department of Radiology, Patan Hospital, among patients diagnosed with CRS who underwent paranasal sinus (PNS) CT scans. MSV were measured using CT imaging software, and the presence and severity of DNS were documented. Statistical analysis was performed using SPSS v 20. Result: Among the patients, 237 (78.2%) had DNS, predominantly on the right side (54.0%). The mean MSV was significantly smaller on the deviated side (13.21±2.98 cm³) compared to the contralateral side (14.56±3.15 cm³, p<0.001). Increasing DNS severity was associated with progressive reduction in MSV (mild: 0.58 ± 0.61 cm³; moderate: 1.63±0.85 cm³; severe: 3.07±1.22 cm³; p<0.001). A strong negative correlation was found between deviation angle and ipsilateral MSV (r=–0.62, p<0.001). Mucosal thickening occurred in 84.2% of patients, mainly on the deviated side (62.4%, p=0.002), and was more frequent in moderate-to-severe deviations. Pyramidal sinus morphology predominated, with no significant right–left differences in patients without DNS Conclusion: DNS significantly reduces ipsilateral sinus volume and increases mucosal changes. CT-based volumetric evaluation and septal assessment are vital for CRS diagnosis and surgical planning.